STRUCTURE CHARACTERIZATION OF FLAVONOID Aglycone FROM ETHYL ACETATE EXTRACT OF Rhodomyrtus tomentosa (AIT) HASSK - Rizal Fahmi; Yunazar Manjang; Dachriyanus -; Nordin Lajis (Universitas Andalas, 2011)
ABSTRACT A flavonoid aglycone, 5-hydroxy-3,3’,4’,5’,7 pentamethoxy - flavone (Combretol), an antibacterial compound of ethyl acetate extract from the leaves of Rhodomyrtus tomentosa. The structure of this compound was established based on spectroscopic analyses and comparison with the related compound. The structure characterization of this compound will be discussed. Keywords: Rhodomyrtus tomentosa, flavonoid aglycone, structure characterization